2008
DOI: 10.1007/s11162-008-9113-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to Part-time Faculty on Community College Transfer

Abstract: Over the past several decades, one of the most significant changes in the delivery of postsecondary education involves the dramatic increase in the use of contingent or part-time faculty. Although the increased use of part-time faculty within higher education makes sense from an administrative point of view, its use does not come without criticism. With community colleges representing a more convenient, affordable, and flexible educational option for a number of students, particularly those from disadvantaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(14 citation statements)
references
References 38 publications
0
12
2
Order By: Relevance
“…These figures reflect the tremendous range of advising resources available to community college students at different institutions, which have been found to predict students’ transfer and attainment outcomes (Bahr 2008). Research has also found that students are less likely to transfer the more they are exposed to part-time or adjunct faculty (Calcagno et al 2008; Eagan Jr. and Jaeger 2009) and the larger the size of the institution (Calcagno et al 2008).…”
Section: Institutionsmentioning
confidence: 99%
“…These figures reflect the tremendous range of advising resources available to community college students at different institutions, which have been found to predict students’ transfer and attainment outcomes (Bahr 2008). Research has also found that students are less likely to transfer the more they are exposed to part-time or adjunct faculty (Calcagno et al 2008; Eagan Jr. and Jaeger 2009) and the larger the size of the institution (Calcagno et al 2008).…”
Section: Institutionsmentioning
confidence: 99%
“…The majority of empirical work around 2-year college student pathways focuses on upward or vertical transfer, with an abundance of literature examining individual factors (e.g., Adelman, 1999; Bailey, Jenkins, & Leinbach, 2005; Crisp & Nuñez, 2014; Dougherty & Kienzl, 2006; LaSota & Zumeta, 2016; Roksa, 2006; Wang, 2013) or institutional factors (e.g., Bahr, 2010; Bailey et al, 2005; Crisp & Delgado, 2014; Eagan & Jaeger, 2009; LaSota & Zumeta, 2016; Porchea, Allen, Robbins, & Phelps, 2010; Roksa, 2006) that relate to students’ likelihood of transferring vertically. Other researchers have explored 2-year college students’ experiences before and adjustment after vertical transfer (e.g., Laanan, 2007; Laanan, Starobin, & Eggleston, 2010; Starobin & Laanan, 2008; Vasquez Urias, Falcon, Harris, & Wood, 2017; Wilson, 2014) and post-transfer outcomes (e.g., Andrews, Li, & Lovenheim, 2014; Lee & Schneider, 2016; Melguizo & Dowd, 2009; Wang, 2009).…”
Section: Relevant Literature and Frameworkmentioning
confidence: 99%
“…By identifying particular faculty behaviors that predict student learning, and by focusing on the types of faculty that employ those strategies in their courses, we provide greater detail to understanding the ways faculty behaviors relate to community college student learning. Our finding that full-time faculty and faculty with more course teaching experience engage more frequently in productive teaching practices might explain Eagan and Jaeger’s (2009) finding that community college students’ likelihood of completing an associate degree was slightly lowered when they took courses with part-time instructors. Our findings raise the question about whether the issue is about part-time instruction or whether it is about teaching experience.…”
Section: Discussionmentioning
confidence: 72%